FOREST Unbiased Galactic plane Imaging survey with the Nobeyama 45 m telescope (FUGIN): Molecular clouds toward W 33; possible evidence for a cloud–cloud collision triggering O star formation. (11th January 2018) - Kohno, Mikito; Torii, Kazufumi; Tachihara, Kengo; Umemoto, Tomofumi; Minamidani, Tetsuhiro; Nishimura, Atsushi; Fujita, Shinji; Matsuo, Mitsuhiro; Yamagishi, Mitsuyoshi; Tsuda, Yuya; Kuriki, Mika; Kuno, Nario; et al.
Abstract: We observed molecular clouds in the W 33 high-mass star-forming region associated with compact and extended H ii regions using the NANTEN2 telescope as well as the Nobeyama 45 m telescope in the J = 1–0 transitions of 12 CO, 13 CO, and C 18 O as part of the FOREST Unbiased Galactic plane Imaging survey with the Nobeyama 45 m telescope (FUGIN) legacy survey. We detected three velocity components at 35 km s −1, 45 km s −1, and 58 km s −1 . The 35 km s −1 and 58 km s −1 clouds are likely to be physically associated with W 33 because of the enhanced 12 CO J = 3–2 to J = 1–0 intensity ratio as R_3-2/1-0 > 1.0 due to the ultraviolet irradiation by OB stars, and morphological correspondence between the distributions of molecular gas and the infrared and radio continuum emissions excited by high-mass stars. The two clouds show complementary distributions around W 33. The velocity separation is too large to be gravitationally bound, and yet not explained by expanding motion by stellar feedback. Therefore, we discuss whether a cloud–cloud collision scenario likely explains the high-mass star formation in W 33.